Długofalowe zmiany nierówności dochodów, ich społeczna doniosłość oraz związek z rozwojem gospodarczym – w perspektywie europejskiej i globalnej - Janusz T. Hryniewicz (Ksiegarnia Akademicka Publishing, 2019)
Long Term Changes of Income Inequalities, Their Social Importance and Relationship With Economic Development – in the European and Global Perspective Data analysis based on Gini index proves that income inequalities were growing in the 1980s and 1990s and next, mixed trends prevailed, with the exception of fast growth in the incomes of 1% top richest households. In spite of the fact that the expansion of knowledge-based economy has begun in the same time as income inequality growth, there are no direct connection between these two phenomena. The intermediary factor is financial capitalism. Innovations created in new economy (ICT) encourage the development of financial capitalism and quick growth of 1% of the highest incomes. The social importance of inequality growth is very low. The growth of income inequalities very slightly changes the evaluation of the existing income inequalities. The increase of salary inequality has not diminished work motivation in European enterprises. The growth of financial capitalism has encouraged growth of venture capital investment in sectors of knowledge-based economy.